Improving Landfill Liner Performance through Mitigating Desiccation Cracking Using Fiber and Nanocomposite Materials: A Laboratory Study - Hojat Dehestani; Abdolhosein Haddad (Journal of Rehabilitation in Civil Engineering)
Landfill liners are critical components of waste management infrastructure, designed to prevent the migration of leachate into the surrounding environment. However, the long-term performance of these liners is significantly influenced by their susceptibility to desiccation cracking. This study investigated the effectiveness of incorporating polypropylene composites, micro-silica, and nano-silica as additives within the clay liner material to mitigate cracking and enhance overall liner performance. Three distinct clay types were evaluated: local soil, soil excavated from the landfill site, and a synthetic clay mixture. Laboratory experiments were conducted to assess the impact of the additives on crack formation and by extension, the hydraulic conductivity of the liner material. The results demonstrated a significant reduction in crack formation across all clay types with the addition of 0.8% polypropylene. Similarly, incorporating 20% micro-silica exhibited a marked decrease in cracking, suggesting a potential improvement in the long-term hydraulic performance of the liner. These findings indicate that the inclusion of these additives can enhance the resistance of the clay liner to desiccation, thereby minimizing the risk of leachate migration and contributing to the environmental integrity of the landfill site. This research has important implications for the design and construction of more robust and environmentally sound landfill liners. Further research is warranted to optimize the concentration and combination of these additives, evaluate their long-term performance under field conditions, and assess their cost-effectiveness in improving the overall durability and environmental performance of landfill liners.